(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the level of both self-awareness and beyond emotion and the correlation between them among university students, and for the purpose of achieving the goals, tools were prepared that measure what they came for and then were applied to a sample of university students. And that the relationship between them is direct, and the researcher recommended some recommendations and suggested what he deems appropriate